2018
DOI: 10.1155/2018/4851645
|View full text |Cite
|
Sign up to set email alerts
|

Climate Changes and Associated Multiscale Impacts on Watershed Discharge over the Upper Reach of Yarlung Zangbo River Basin, China

Abstract: Watershed discharge (WD) in the alpine regions, such as the upper reach of Yarlung Zangbo River Basin (YZRB), China, could have changed severely in response to climate changes. Yet, how hydrometeorological variables varied at different time scales and how WD varied in response to hydrometeorological variables in the alpine regions remained questions to be answered. The ensemble empirical mode decomposition (EEMD) method was employed in this study to investigate the nonlinear climate change trends (averaged and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 35 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…where p(k j | q i ) = k(q i , k j ) /(∑ l k(q i , k l )), and k(q i , k j ) selects the asymmetric exponential kernel exp (q i k T j )/ √ d [23]. To measure the sparsity of Query, Informer uses Kullback-Leibler divergence.…”
Section: Self-attention Mechanism Of Informer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where p(k j | q i ) = k(q i , k j ) /(∑ l k(q i , k l )), and k(q i , k j ) selects the asymmetric exponential kernel exp (q i k T j )/ √ d [23]. To measure the sparsity of Query, Informer uses Kullback-Leibler divergence.…”
Section: Self-attention Mechanism Of Informer Modelmentioning
confidence: 99%
“…Through a comparison of the forecasting results of various models with actual observations, the study found that the models based on the integration methods have higher accuracy and stability relative to the single models. Xu et al [22] combined Complementary Ensemble Empirical Mode Decomposition (CEEMD) and ARIMA, and they showed that the CEEMD-ARIMA model was applicable to drought prediction; the model could also identify multiple modalities of drought variability on diverse timescales [23], improving the comprehensiveness and accuracy of the prediction.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that all the observations used in CPAP have undergone strict quality control (QC), including extrema detection, internal consistency check, and spatial consistency check, before applying the OI technique [60,61]. In recent years, the CPAP has been widely used in precipitation-related (e.g., drought and runoff) investigations in China [62][63][64], particularly as reference data to validate high temporal and spatial resolution satellite-based precipitation products [59,65,66]. As a result, this research used it as a benchmark for comparing precipitation measurements with GCMs from 1961-2014.…”
Section: Reference Precipitation Observationsmentioning
confidence: 99%